Biology, Ecology, and Management of Masked Chafer (Coleoptera: Scarabaeidae) Grubs in Turfgrass. (10th February 2016) - Gyawaly, S.; Koppenhöfer, A. M.; Wu, S.; Kuhar, T. P.
Abstract: Masked chafers are scarab beetles in the genus Cyclocephala. Their larvae (white grubs) are below-ground pests of turfgrass, corn, and other agricultural crops. In some regions, such as the Midwestern United States, they are among the most important pest of turfgrass, building up in high densities and consuming roots below the soil/thatch interface. Five species are known to be important pests of turfgrass in North America, including northern masked chafer, Cyclocephala borealis Arrow; southern masked chafer, Cyclocephala lurida Bland [formerly Cyclocephala immaculata (Olivier)]; Cyclocephala pasadenae (Casey); Cyclocephala hirta LeConte; and Cyclocephala parallela Casey. Here we discuss their life history, ecology, and management.